Crossover comparison of ferumoxytol and gadobenate dimeglumine for abdominal MR‐angiography at 3.0 tesla: Effects of contrast bolus length and flip angle. Issue 6 (10th November 2016) - Schubert, Tilman; Motosugi, Utaroh; Kinner, Sonja; Colgan, Timothy J.; Sharma, Samir D.; Hetzel, Scott; Wells, Shane; Campo, Camilo A.; Reeder, Scott B.
Abstract : Purpose: Ferumoxytol (FE) has gained interest as an alternative to gadolinium‐based contrast agents (GBCAs). The purpose of this study was to evaluate and optimize ferumoxytol dose and T1 weighting, in comparison to a conventional GBCA. Materials and Methods: Twelve healthy volunteers (six women / six men, mean age 44.3 years) were recruited for this study. Scanning was performed on a clinical 3 Tesla (T) MRI system. Gadobenate dimeglumine (GD)‐enhanced MRA was performed followed by FE‐enhanced MRA 1 month later. Volunteers were randomly assigned to a diluted (n = 6) or undiluted (n = 6) dose of GD (0.1 mmol/kg), and to FE doses of 4 mg/kg (n = 6) or 2 mg/kg (n = 6). First pass and steady‐state MRA were performed for GD‐ and FE‐enhanced MRA. Flip‐angle optimization was performed after FE administration. Quantitative analysis included relative contrast‐to‐noise ratio (relCNR) measurements for all acquisitions. First pass GD‐ and FE‐enhanced MRA images were evaluated qualitatively. Results: RelCNR was significantly higher with undiluted GD (31.8, 95% confidence interval [CI], 27.7–35.9) compared with diluted GD (16.2; 95% CI, 12.2–20.3; P  = 0.001) and both 4 mg/kg FE (12.5; 95% CI, 8.5–16.4; P  < 0.001) and 2 mg/kg FE (9.1; 95% CI, 5.1–13.2; P  < 0.001) during first pass. Relative CNR did not decrease with FE 5 min postinjection compared with GD. Flip‐angle analysis revealed relative CNR‐peaks at 30° for FE 4 mg/kg and at 20° for FE 2 mg/kg. Diluted GD ( P  = 0.013) and FE 4 mg/kg ( P  = 0.01) revealed significantly higher image quality scores compared with undiluted GD during first pass. Conclusion: This study shows an equivalent image quality of FE and GD for first pass MRA even though GD showed significantly higher relative CNR. Level of Evidence : 1 Technical Efficacy : Stage 2 J. MAGN. RESON. IMAGING 2017;45:1617–1626